Studying Organization : Theory and Method. - Clegg, Stewart R., 1947- (Sage Publications, 1999)
In response to the needs of lecturers, the acclaimed Handbook of Organization Studies has been made available as two major paperback textbooks. In this, the first of a two-volume paperback edition of the landmark Handbook of Organization Studies, editors Stewart Clegg and Cynthia Hardy survey the field of organization studies. Studying Organization is an ideal textbook around which to build courses on organization theory and research methodology. Central to the enterprise has been a concern to reflect and honour the manifest diversity of the field, including recognition of the extent to which.